2017
DOI: 10.1016/j.ypmed.2016.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Objectively-measured physical activity in children is influenced by social indicators rather than biological lifecourse factors: Evidence from a Brazilian cohort

Abstract: The aim of this study was to examine the longitudinal influences of early life social and biological indicators on objectively measured physical activity. All newborns in 2004 in the city of Pelotas, Southern Brazil were enrolled in a birth cohort study. At the age of 6 years, a follow-up visit included objective assessment of overall physical activity (summarized in milli-g, 1 mg = 0.001 g) by tri-axial wrist worn accelerometry. The associations between early life exposures, such as type of delivery, parity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…The publication date of the selected studies ranged from 2008 to 2018. Seven of the included studies were conducted in the South region of Brazil 11,[13][14][15][16][17][18] , three studies in the Southeast region [19][20][21] and three studies in the Northeast region [22][23][24] .…”
Section: Resultsmentioning
confidence: 99%
“…The publication date of the selected studies ranged from 2008 to 2018. Seven of the included studies were conducted in the South region of Brazil 11,[13][14][15][16][17][18] , three studies in the Southeast region [19][20][21] and three studies in the Northeast region [22][23][24] .…”
Section: Resultsmentioning
confidence: 99%
“…As previously noted, early-life social and family circumstances are associated with inactivity at 50y but not 33y ( Pinto Pereira et al, 2014a ) and with inactivity persistence and deterioration but not improvement ( Pinto Pereira et al, 2015 ). Our findings for parental divorce (early-life family) are novel in light of the limited evidence available, while findings for social background add to the sparse literature including recent research in children ( Knuth et al, 2017 ). Previously, we hypothesized that parents' manual work may not be conducive to physical activity during leisure-time, with transmission of behaviour to offspring ( Pinto Pereira et al, 2014a ).…”
Section: Discussionmentioning
confidence: 55%
“…Several studies have investigated the association between BW and PA in children and adolescents. 24 , 34 Gopinath et al 18 showed that children aged 12 years with low BW participate in less outdoor PA. Although the exact mechanisms for the difference in time spent in PA between low- and normal-BW individuals are unknown, previous studies have shown that low BW could be related to reduced physical capacity, including reduced muscle strength 35 and insufficient anaerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, other studies that objectively measured PA with an accelerometer did not confirm the association between BW and PA in children and adolescents. 24 , 34 It is possible that objective measures of PA and self-reported PA are capturing different aspects of PA. A previous study suggested that self-reported PA may capture only specific types of exercise and leisure-time PA, whereas accelerometers measure all body movement throughout a measurement period. 41 Although sex was adjusted for in all of these studies, PA levels between boys and girls is markedly different.…”
Section: Discussionmentioning
confidence: 99%